2022
DOI: 10.1111/evo.14478
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive divergence generates distinct plastic responses in two closely related Senecio species

Abstract: The evolution of plastic responses to external cues allows species to maintain fitness in response to the environmental variations they regularly experience. However, it remains unclear how plasticity evolves during adaptation. To test whether distinct patterns of plasticity are associated with adaptive divergence, we quantified plasticity for two closely related but ecologically divergent Sicilian daisy species (Senecio, Asteraceae). We sampled 40 representative genotypes of each species from their native ran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 70 publications
3
27
0
Order By: Relevance
“…Although plasticity will be adaptive for environments where the plastic responses maintain high fitness, it may fail to be so in a novel or highly stochastic environment, which suggests that the relationship between adaptiveness and plasticity is variable and more complex than a simple linear relationship (Pfennig 2021). In this study, Walter et al (2022) confirmed that adaptive divergence can lead to differences in plasticity over a comparatively short timescale (∼150,000 years) and analyzed the adaptiveness of these changes in plasticity. Walter et al (2022) studied the evolution of phenotypic plasticity in two ecologically divergent but genetically similar Sicilian daisy species from Mt.…”
supporting
confidence: 58%
See 4 more Smart Citations
“…Although plasticity will be adaptive for environments where the plastic responses maintain high fitness, it may fail to be so in a novel or highly stochastic environment, which suggests that the relationship between adaptiveness and plasticity is variable and more complex than a simple linear relationship (Pfennig 2021). In this study, Walter et al (2022) confirmed that adaptive divergence can lead to differences in plasticity over a comparatively short timescale (∼150,000 years) and analyzed the adaptiveness of these changes in plasticity. Walter et al (2022) studied the evolution of phenotypic plasticity in two ecologically divergent but genetically similar Sicilian daisy species from Mt.…”
supporting
confidence: 58%
“…In this study, Walter et al (2022) confirmed that adaptive divergence can lead to differences in plasticity over a comparatively short timescale (∼150,000 years) and analyzed the adaptiveness of these changes in plasticity. Walter et al (2022) studied the evolution of phenotypic plasticity in two ecologically divergent but genetically similar Sicilian daisy species from Mt. Etna, Senecio chrysanthemifolius, native to disturbed habitats 400-1000 m above sea level, and Senecio aethnensis, endemic to lava flows 2000-2600 m above sea level.…”
supporting
confidence: 58%
See 3 more Smart Citations